Tri-Factor Analysis of Financial Sustainability: ROA, Firm Size, and NPL in Rural Banks in Riau Province - Hanafi, Imam; Hidayat, Hidayat; Pratama, Dani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to identify the factors influencing Financial Sustainability in Rural Banks in Riau Province. The study assesses whether Return On Assets (ROA), Firm Size, and Non-Performing Loan (NPL) have an impact on Financial Sustainability in Rural Banks in Riau Province. The population of this study consists of 34 Rural Banks, with purposive sampling techniques selecting a total of 23 Rural Banks that meet the sample criteria. Data analysis is conducted using Ordinary Least Squares through EViews 12, utilizing panel data spanning from 2018 to 2022. The research findings indicate that Return On Assets (ROA), Firm Size, and Non-Performing Loan (NPL) significantly influence Financial Sustainability in Rural Banks in Riau Province.